Persoalan dan Konstruksi Norma Pengaturan Pembatasan Kebebasan Berkumpul Di Indonesia - Mirza Satria Buana; Wahyudi Djafar; Ellisa Vikalista (Jurnal Hukum IUS QUIA IUSTUM, 2021)
This article analyzes normative issues in various laws and regulations governing the handling of freedom of peaceful assembly. The formulations of the problems analyzed in this article are: first, whether the regulation and limitation of the right to peaceful assembly in Indonesia are in line with international human rights ideals. Second, how are the arrangements and restrictions on the right of assembly from other countries, which can provide constructive input on the norms for regulating and limiting the freedom of peaceful assembly in Indonesia? This article uses normative legal research and a comparative approach to constitutional law, by looking at concepts and practices from other countries. The conclusions of this study are: first, the regulation and restriction of the freedom of peaceful assembly is still far from the ideal of international human rights. There are still ambivalent and discriminatory arrangements. Second, the conclusion from the results of the comparative study found that there are many variants of gathering activities that are not accommodated by Indonesian legislation, such as: sudden gatherings, continuous and scheduled gatherings, and reciprocal gatherings.